Seesaw protein: Design of a protein that adopts interconvertible alternative functional conformations and its dynamics - Toma Ikeda; Tatsuya Nojima; Souma Yamamoto; Ryusei Yamada; Tatsuya Niwa; Hiroki Konno; Hideki Taguchi (Proceedings of the National Academy of Sciences, 2025)
According to classical Anfinsen’s dogma, a protein folds into a single unique conformation with minimal Gibbs energy under physiological conditions. However, certain proteins may fold into two or more conformations from single amino acid sequences. Here, we designed a protein that adopts interconvertible alternative functional conformations, termed “seesaw” protein (SSP). An SSP was engineered by fusing GFP lacking the C-terminal β-strand and dihydrofolate reductase (DHFR) lacking the N-terminal β-strand with an overlapping linker, which can be competitively incorporated into either the GFP or the DHFR moiety. In vivo and biochemical analyses, including atomic force microscopy (AFM) imaging, demonstrated that the SSP adopts two alternative conformations, which can be biased by point mutations and ligand binding. The drastic conformational change upon the ligand binding was directly visualized by high-speed AFM. Furthermore, the balance of the seesaw can be reversibly changed depending on buffer conditions. In summary, our design strategy for SSP provides a unique direction for creating artificial proteins with on–off behaviors.